Custos da mão de obra: comparação entre contratação por meio da terceirização e da consolidação das leis trabalhistas - Felkicher, Eduarda Rodrigues (2024)
The construction industry plays a crucial role in the Brazilian economy, generating a significant amount of direct and indirect jobs. One of the main challenges faced is the high cost of labor. To deal with these challenges, construction companies have sought to diversify the hiring models for their workers. In this way, it presents a study on two models of labor hiring in a project carried out in the city of Toledo/PR. A detailed budget was carried out, as well as a survey of the worker's productivity, identification of labor costs in the municipality of Toledo in Paraná, considering social charges, and a survey of outsourced labor prices. As a result, a cost for the execution of the project was reached for the consolidated labor in the labor laws, which was 14.31% higher than the cost of outsourced labor, with a significant difference in the stages of preliminary services, foundations and coatings. Thus, the importance of an evaluation by professionals when selecting the model for hiring labor for the execution of a project is highlighted.